Acoustic Characterization of Fluorinert FC-43 Liquid with Helium Gas Bubbles: Numerical Experiments - Christian Vanhille; Cristian Pantea; Dipen N. Sinha (Shock and Vibration)
In this work, we define the acoustic characteristics of a biphasic fluid consisting of static helium gas bubbles in liquid Fluorinert FC-43 and study the propagation of ultrasound of finite amplitudes in this medium. Very low sound speed and high sound attenuation are found, in addition to a particularly high acoustic nonlinear parameter. This result suggests the possibility of using this medium as a nonlinear enhancer in various applications. In particular, parametric generation of low ultrasonic frequencies is studied in a resonator cavity as a function of driving pressure showing high conversion efficiency. This work suggests that this medium could be used for applications such as parametric arrays, nondestructive testing, diagnostic medicine, sonochemistry, underwater acoustics, and ultrasonic imaging and to boost the shock formation in fluids.